Redescriptions of five of Takahashi’s soft scale species (Hemiptera: Coccomorpha: Coccidae) with comments on their status and relationships - Hodgson, Chris J. (Zootaxa, 2023)
This paper redescribes and illustrates five currently poorly known species of soft scale insect (Hemiptera: Coccomorpha: Coccidae) originally described by Ryoichi Takahashi, namely Coccus lumpurensis Takahashi, Maacoccus scolopiae (Takahashi), Membranaria sacchari (Takahashi), Platylecanium cyperi Takahashi and P. mesuae Takahashi. Lectotypes are designated for C. lumpurensis, P. cyperi and P. mesuae. Two of these species are known only from Taiwan, and three from Malaysia. Their status and relationships are discussed. A key to the species of Maacoccus is included.